Performance evaluation of novel 9-level RSMLI topology for grid-tied solar-PV system - Sharma, Pidatala Prabhakara; Rao, Lingineni Shanmukha; Amulya, Goddanti (International Journal of Applied Power Engineering (IJAPE), 2024)
The shortage of traditional fossil fuels like coal, petrol and natural-gas are increased day-by-day, fulfills the most of energy demand. Most of engineers are trying to maximize the energy demand by employing renewable energy with existing micro-grid system. Owing to merits, the solar-PV system plays a significant alternative among all other renewable energy sources due to abundant and virtuous nature. For grid-tied solar-PV system, the cascaded H-bridge multilevel inverter is the most significant over the classical 2-level inverter due to provision of isolated input DC sources. But the cascaded H-bridge topology is designed for limited voltage levels due to its larger number of switches for higher voltage levels, high cost, large-size, and more weight. To alleviate these demerits, a reduced-switch multilevel inverter has been generally preferable for higher voltage levels. In this work, a novel 9-level reduced-switch multilevel inverter (RSMLI) topology has been proposed by utilizing low number of switching devices. The performance of proposed novel 9-level RSMLI topology has been verified in grid-tied solar-PV system by using MATLAB/Simulink tool, simulation results are presented with attractive comparisons.